Tying governments' hands in commodity taxation - Ludger Schuknecht (World Trade Organization (WTO), 1998)
In the 1970s, taxation of windfall profits from primary products and intervention in trade and production has tempted governments into expansionary fiscal policies while stifling the private sector and depressing growth. However, the experience of the recent coffee boom has so far been more favourable: those African countries which liberalized and left a large share of the windfall with the private sector, and which committed themselves to fiscal austerity via adjustment programs have shown better results in terms of fiscal stability, private sector responses and economic growth than countries which did not reform. These findings suggest that constraints on discretionary government policies are desirable, and domestic institutions and international commitments could serve such purpose.
Keywords: E62; F13; H30; O55; 330; Commodity booms; terms of trade; political economy; fiscal policies; export taxes; public expenditure; savings and investment; Africa